Ultrabreathable and Protective Membranes with Sub‐5 nm Carbon Nanotube Pores. Issue 28 (9th May 2016) - Bui, Ngoc; Meshot, Eric R.; Kim, Sangil; Peña, José; Gibson, Phillip W.; Wu, Kuang Jen; Fornasiero, Francesco
Abstract : Small‐diameter carbon nanotubes (CNTs) are shown to enable exceptionally fast transport of water vapor under a concentration gradient driving force. Thanks to this property, membranes having sub‐5 nm CNTs as conductive pores feature outstanding breathability while maintaining a high degree of protection from biothreats by size exclusion.